Pengembangan Aplikasi Penilaian Kinerja Guru Berbasis Web Pada SMP El Mundo Kota Jambi - Yulvianda, Renaldi; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2021)
El Mundo Junior High School in Jambi City is currently improving the quality of service in the teaching category and realizes how important the application of technology is in data and information management, especially in the teacher performance assessment system. This occurs because of a problem, namely the assessment of teacher performance is currently carried out using a paper based method and the results will be recapitulated to the Microsoft Excel application provided by the education authorities. So this is prone to basic errors such as scattered files, wrong input or easily damaged and the data management process to become information is relatively slow and cannot be known transparently. The purpose of this research is to create a teacher performance assessment application so that it helps schools in managing data and becomes the basis for information for making decisions. Data collection was carried out by interviewing the school. In addition, the system development method used is a waterfall with UML (Unified Modeling Language) and Adobe XD tools to design a user interface and use the PHP programming language with the Laravel framework. The output of this research is a web-based teacher performance assessment application at El Mundo Junior High School, Jambi City.